(untitled) (Web of Teachers: Inderscience Research, 2025)
This article examines the idea of cognitive linguistics, a branch of linguistics that is strongly associated with neurolinguistics and psycholinguistics. The study of cognitive linguistics examines the relationship and mutual interaction between language and thought. The relationship between language’s semantic structures and cognitive functions, as well as how they influence how people see the world, are the main topics. The foundation of cognitive linguistics is the notion that language is more than just a collection of signs; it also represents the mental processes by which individuals view and understand the world. This line of inquiry focuses on the connections between the different categories and concepts found in language and more general cognitive systems. The study of the relationship between language and the cultural and cognitive traits of particular societies is one of the key facets of cognitive linguistics. Several schools are taken into consideration in this context, each offering a unique perspective on how to comprehend language as a component of the cognitive picture of the world. Every school investigates how language affects how people see and understand the world, as well as how they interact with one another and the environment.